Adverse Childhood Experiences and Prescription Stimulant Use in Adults: A Systematic Review - Avery Beatty; Emily Shepard; Erek Bickford; Lisa Weyandt (MDPI AG, 2024)
Nonmedical prescription stimulant use (NPSU) is an ongoing public health crisis in the United States. There exists, however, a dearth of research investigating specific childhood risk factors that may contribute to this illicit use. Adverse childhood experiences (ACEs) may be a significant risk factor to address in the prevention and treatment of NPSU, as research has provided evidence for increased substance use, potentially including prescription stimulant misuse, among individuals who have experienced trauma. A systematic review of the literature was conducted to gather and synthesize research articles specifically examining the relationship between nonmedical prescription stimulant use in adults and the experience of adverse childhood experiences (ACEs). Four studies met all inclusion criteria and were included in the review. The results demonstrated that the nonmedical use of prescription stimulants in adults is significantly associated with ACEs, with a higher numerical count of ACEs associated with a greater likelihood of nonmedical prescription stimulant use. Gaps in the literature were identified, specifically noting a lack of information available regarding the relationship between ACEs and NPSU within gender- and racially diverse populations. The findings have implications for informing interventions related to ACEs and the misuse of prescription stimulant medication in adults.